Decentralised generation and its role in enhancing the resilience of energy islands and critical infrastructure: Current trends and prospects - Voitenko, Vitalii; Polishchuk, Roman (Technologies and Engineering, 2025)
Threats to critical infrastructure have heightened the relevance of autonomous energy supply and facilitated the transition to decentralised solutions. The study aimed to analyse the theoretical foundations of decentralised generation, its application in energy islands to enhance the resilience of critical infrastructure under emergency conditions. The methodological framework of the research included a theoretical synthesis of contemporary scientific approaches, real-world case studies of renewable technology development and autonomous energy supply models in the US, EU, and Ukraine, as well as a comparative analysis of autonomous energy supply models. The results demonstrated that solar and hybrid (solar-biogas) systems proved most effective. In Ukraine, over 5,000 residential solar installations were deployed in 2023, while in the village of Nyzhniy Bystryy (Zakarpattia), a hybrid energy island supplied electricity to 120 households. In the US, solar generation increased by 16% in 2023, with a 40% growth recorded in 2024. In the EU, the average levelised cost of solar electricity production decreased by 12% in 2023. In Tuscany (Italy), an energy island restored power supply within 12 hours in 2022 compared to 72 hours in the centralised system. In Ukraine, decentralised generation reduced recovery time to 3-6 hours in frontline regions (versus 12-18 hours traditionally), with electricity costs at 0.08 USD/kWh compared to 0.12 USD/kWh in the centralised system. The study revealed that decentralised generation enhanced grid flexibility and resilience by reducing transmission losses (up to -10%) and diversifying supply sources. Innovative technologies (digital control, artificial intelligence) were found to improve dispatching efficiency, enabling energy islands and microgrids to autonomously power critical facilities even during total grid collapse. The practical significance of the research lies in applying its findings to energy security strategies, microgrid development, and planning autonomous systems in vulnerable regions